2017
DOI: 10.3892/etm.2017.5054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of docosahexaenoic acid on traumatic brain injury in rats

Abstract: Abstract. The present study aimed to investigate the protective effects of docosahexaenoic acid (DHA) on traumatic brain injury (TBI) in rats. A model of TBI was induced by lateral fluid percussion injury in adult rats and rats were randomly divided into the TBI-model group, TBI-low DHA group and TBI-high DHA group, while other healthy rats were assigned to the sham-operated group. Motor recovery was tested with beam-walking trials at 2, 7 and 15 days post-TBI. Cognitive recovery was tested with Morris water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Moreover, docosahexaenoic acid (DHA), which has been shown to inhibit JNK, rescued TBI-mediated hippocampal long-term potentiation (LTP) and improved hippocampus-dependent learning and memory as well as enhanced motor function ( Zhu W. et al, 2019 ). These results are in line with previous studies demonstrating that neuronal dysfunction was alleviated by DHA ( Zhu et al, 2017 , 2018 ). A natural supplementation of blueberry for 2 weeks showed mitigated loss of spatial learning and memory performances and improved anxiety ( Krishna et al, 2019 ), associated to increased expression of BDNF, which plays crucial role in neural maturation, and activated CAMKII ( Krishna et al, 2019 ).…”
Section: The Wnt Pathway In Tbisupporting
confidence: 93%
“…Moreover, docosahexaenoic acid (DHA), which has been shown to inhibit JNK, rescued TBI-mediated hippocampal long-term potentiation (LTP) and improved hippocampus-dependent learning and memory as well as enhanced motor function ( Zhu W. et al, 2019 ). These results are in line with previous studies demonstrating that neuronal dysfunction was alleviated by DHA ( Zhu et al, 2017 , 2018 ). A natural supplementation of blueberry for 2 weeks showed mitigated loss of spatial learning and memory performances and improved anxiety ( Krishna et al, 2019 ), associated to increased expression of BDNF, which plays crucial role in neural maturation, and activated CAMKII ( Krishna et al, 2019 ).…”
Section: The Wnt Pathway In Tbisupporting
confidence: 93%
“…Chen Xiaobo et al [ 11 ] found that DHA played a protective role in cerebral microvascular endothelial cells and astrocytes in rats with oxysugar/sugar deficiency. In the TBI rat models, Zhu W et al [ 12 ] pointed out that DHA prevented neuron death and alleviated TBI injury through regulating apoptosis-related proteins. Moreover, DHA has been verified to provide neuroprotection for the TBI rats by activating nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of inclusion and exclusion criteria to titles and abstracts of search resulted in 201 full‐text articles that were screened for eligibility; 43 journal articles (Bailes & Mills, 2010; Cheng et al., 2016; Cole et al., 2010; Davis et al., 2008; Deng‐Bryant et al., 2011; Elliott et al., 2018; Gerbatin et al., 2019; Greco et al., 2016; Hu, Wang, Jin, et al., 2009; Hu, Wang, Qiao, et al., 2009; Itoh et al., 2013; Ji et al., 2017; Jiang et al., 2017; Krishna et al., 2019; Kumar et al., 2014; Lim et al., 2013; Liu et al., 2017; Mills et al., 2011; Ozbal et al., 2015; Özevren et al., 2018; Prins et al., 2005; Prins & Hovda, 2009; Rubovitch et al., 2019; Saraiva et al., 2012; Schober et al., 2016; Schwartzkroin et al., 2010; Sharma et al., 2010; Shin & Dixon, 2011; Su et al., 2016; Thau‐Zuchman et al., 2019; Toklu et al., 2009; Wang et al., 2018; Wang, Li, et al., 2016; Wang, Zhang, et al, 2016; Wei et al., 2015; Wu et al., 2011, 2014; Xie et al., 2018; Xing et al., 2016; Xu et al., 2017; Zhang et al, 2018; Zhao et al., 2014; Zhu et al., 2017) met all eligibility criteria. Most studies (28/43) were conducted since 2013, with four to seven new studies being released each year since 2016.…”
Section: Resultsmentioning
confidence: 99%
“… natural compounds with known anti‐oxidant properties (Cheng et al., 2016; Itoh et al., 2013; Ji et al., 2017; Jiang et al., 2017; Krishna et al., 2019; Ozbal et al., 2015; Toklu et al., 2009; Wei et al., 2015); branched chain amino acids (BCAA) (Cole et al., 2010; Elliott et al., 2018; Lim et al., 2013); creatine (Gerbatin et al., 2019; Saraiva et al., 2012); fasting and caloric restriction (Davis et al., 2008; Liu et al., 2017; Rubovitch et al., 2019); KD (Deng‐Bryant et al., 2011; Greco et al., 2016; Hu, Wang, Jin, et al., 2009; Hu, Wang, Qiao, et al., 2009; Prins et al., 2005; Prins & Hovda, 2009; Schwartzkroin et al., 2010; Zhang et al., 2018); multi‐supplements (Thau‐Zuchman et al., 2019; Wu et al., 2014); ω‐3 polyunsaturated fatty acids (PUFAs) (Bailes & Mills, 2010; Mills et al., 2011; Schober et al., 2016; Shin & Dixon, 2011; Su et al., 2016; Wu et al., 2011; Zhu et al., 2017); or natural compounds used in traditional eastern medicine (Kumar et al., 2014; Özevren et al., 2018; Sharma et al., 2010; Wang et al., 2018; Wang, Fan, et al, 2016; Wang, Zhang, et al, 2016; Xie et al., 2018; Xing et al., 2016; Zhao et al., 2014). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation